The ayakashi hunter's tainted bride. 3 - Yuma, Midori (Kodansha USA Publishing, LLC, 2025)
The reason why Nanao has not disposed of the hairpin from her former fiance, Reito, is revealed to Yako. Already knowing Nanao's feelings, Yako asks for her to choose him. Once again, the two reaffirm their mutual feelings for each other and strengthen their bond. Sleeping by each other's side, a taste of chocolate... all these first times are fleeting. Unfortunately for Akemi, Reito wants to end his marriage with her as his eyes turn back toward Nanao...